2022
DOI: 10.1371/journal.pone.0266958
|View full text |Cite
|
Sign up to set email alerts
|

Age and sex associations of SARS-CoV-2 antibody responses post BNT162b2 vaccination in healthcare workers: A mixed effects model across two vaccination periods

Abstract: This study aimed to examine the associations with epidemiological, behavioral and clinical parameters of IgG antibody responses against the spike protein of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) after immunization with two doses of the BNT162b2 vaccine in a cohort of healthcare workers (HCWs, n = 439) in Greece. We used a mixed effects model to investigate the potential associations of antibody levels one and three months after vaccination and examined by bootstrapping t-tests the putati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 30 publications
(36 reference statements)
4
17
0
Order By: Relevance
“…The over-representation of females among our participants (30 out of 38 individuals) may have also biased our results, as females are known to differ from males in the induction and waning of antibodies, in both infection and vaccination settings. 22 , 33 , 34 We did not have access to nasopharyngeal swabs to measure antibody levels at the site of viral entry and replication. We were thus unable to link breakthrough infections to local levels of antibodies, which might represent a better correlate of protection.…”
Section: Discussionmentioning
confidence: 99%
“…The over-representation of females among our participants (30 out of 38 individuals) may have also biased our results, as females are known to differ from males in the induction and waning of antibodies, in both infection and vaccination settings. 22 , 33 , 34 We did not have access to nasopharyngeal swabs to measure antibody levels at the site of viral entry and replication. We were thus unable to link breakthrough infections to local levels of antibodies, which might represent a better correlate of protection.…”
Section: Discussionmentioning
confidence: 99%
“…Although males have been shown in some cases to exhibit reduced humoral immunity after vaccination for, or infection with, SARS-CoV-2 [30,31], due to the crucial role of cellular immunity in defense against this virus, a decrease in specific antibodies should be carefully studied and not immediately assumed as a reduction in protection towards severe COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…This increased persistence of SARS-CoV-2 specific antibodies in females, also reported by Søgaard OS [ 28 ], can be explained by the presence of more active B and T cells in older females, resulting in the generation of long-term responses to antigens [ 29 ]. Although males have been shown in some cases to exhibit reduced humoral immunity after vaccination for, or infection with, SARS-CoV-2 [ 30 , 31 ], due to the crucial role of cellular immunity in defense against this virus, a decrease in specific antibodies should be carefully studied and not immediately assumed as a reduction in protection towards severe COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study also suggested that there are individual differences in the antibody response to vaccination. Potential factors are age, gender, and genetics [ 17 ]. Several studies have shown that women and men have an overall similar antibody response after vaccination, however some women have a faster decrease in antibody levels.…”
Section: Discussionmentioning
confidence: 99%